Marketing Communication Strategy Developing for Ban Yangilai and Ban Dongua Occupational Group, Ku Santarat Subdistrict, Mahasarakham District - Phuangchompu Chaiala Sangrungruengroj (วารสารวิทยาการสารสนเทศและเทคโนโลยีประยุกต์, 2020)
This study proposed 1) to study marketing communication model of occupational groups 2) to develop a marketing communication strategy for the occupational group. The mixed research methods used included focus groups, interviews and surveys. The population of this study were splited into 2 groups; the community members of Yangilai and Dongua who were interested in establishing their own occupational group, and the consumer who have bought products from the occupational group. The researcher gathered data from 12 people from the community members 95 people from the consumers using accidental sampling. Statistics used in data analysis were percentage mean and standard deviation.